Crop suitability assessment in remediation of Zn contaminated soil. (May 2020) - Grassi, Chiara; Cecchi, Stefano; Baldi, Ada; Zanchi, Camillo A.; Orlandini, Simone; Pardini, Andrea; Napoli, Marco
Abstract: Zinc (Zn) is naturally present in soils and constitutes an essential micronutrient for plants. Mining, industrial, as well as various agricultural activities all contribute to increasing the Zn concentrations in soils to levels that are toxic for plants. The aim of this study was to evaluate the capacity of field crops to remove Zn from contaminated soils. The experimental design included 28 treatments, comprising seven field crops ( Hordeum vulgare L., Ricinus communis L., Phaseolus vulgaris L., Brassica juncea Czem., S orgum vulgare L., Spinacea oleracea L., Solanum lycopersicum L.) and four Zn levels (0, 500, 1000, 1500 mg kg −1 ) applied to soils. The dry weight (DW) of the aboveground biomass of R. communis and S. lycopersicum increased significantly as the Zn concentration in the soil increased, whereas the DW significantly decreased in P. vulgaris, B. juncea and S. vulgare . Results indicated that S. oleracea was the most efficient in concentrating Zn in the aboveground tissues, followed in decreasing order by H. vulgare, S. lycopersicum, R. communis, S. vulgare, P. vulgaris, and B. juncea . H. vulgare resulted the most efficient in accumulating Zn both in fruit and in leaves and stems, whereas S. lycopersicum resulted the most efficient in accumulating Zn in roots. The BAF and TF values indicated that H. vulgare and S. oleracea resulted being suitable for Zn phytoextraction, whereas the remaining crops being suitable for Zn phytostabilization. These results highlight the phytoremediation potential of the seven analysed crops. Highlights: Spinacea oleracea uptakes Zn up to 1133.1 mg kg-1 in aboveground biomass. Hordeum vulgaris was able to translocate efficiently Zn from roots to aerial tissues. Zn level in the soil influenced the time requirement to reach plant maturity.